STUDI KARAKTERISTIK GAMBAR ANAK-ANAK DI TK NEGERI 2 PADANG - Agung Trimulyana, Drs. Abd. Hafiz, M.Pd, Dra. Ernis, M.Pd. (Universitas Negeri Padang, 2017)
This study aims to determine the characteristics of an image of TK Negeri 2 Padang. This type of research is descriptive qualitative research, the data used in this study are primary data and secondary data and literature study through observation, interviews and documentation. The type in the picture kindergarten children Negeri 2 Padang ie haptic, structural forms, organic, schematic, decorative, enumerative, and ekspresionist. Based on the data above discussion tendency of children to draw with haptic character and expressionist higher than other types of drawing. Colors are often used children in kindergartens in coloring is the tertiary color chartreuse.Kata Kunci : Karakteristik, Gambar, Anak-Anak, TK.